(untitled) (Journal of Asian Development Studies, 2026)
Woman is considered as a sign of attraction in the media. Most the spaces of media are filled by placing the women there. The paper will focus that these spaces are just filled by women just to entertain audience. This paper will focus how the women are represented in satiric shows of Pakistan televised media. It is perceived that the role of women in satiric shows is just as laughter, they are given the place in the satiric show just to fulfill the duty of laughter to entertain the audience. The paper will analyze the who controls the program, what is the role of women in these programs, how much time a women participate in the discussion, and also whether the dummy character presented in these satiric shows are either male or female. This research being carried out to analyze the image and portrayal of women that is being presented in the satiric shows of Pakistan. Content analysis has been used as a research design to measure that how much coverage was given to women in the program.